Camu-camu root distribution underdifferent nitrogen and potassium doses through drip fertigation - Melo, Valdinar Ferreira (2019)
Camu-camu is an native species in domestication processes. Therefore, studies related to the root system are necessary to evaluate the best cultivation practices for an orchard. Two trials were conducted, one with nitrogen (N) and the other with potassium (K), at doses of 0, 40, 80, 160, and 320 kg·ha–1. Root distribution was determined using nondestructive analyses in which two-dimensional (2D) root images were obtained from trenches under the plants’ canopy. Variables included width (measured in cubic millimeters), area (measured in square millimeters), and length (measured in millimeters, and were analyzed using Safira software (version 2010, Embrapa, Brazil). To have better spatial visualization of variable distribution in the soil profile, data were analyzed using the ordinary kriging technique with the geoR software package and R software (version 2016). Both N and K doses influenced positively the camu-camu root system with regard to length, volume, and area. Better root distribution was verified with 80 kg·ha−1 N and 160 kg·ha−1 K doses. The nondestructive analysis via 2D images allowed sound characterization of root spatial distribution.